Understanding fear and anxiety in patients at the time of an exacerbation of chronic obstructive pulmonary disease: a qualitative study. (18th November 2015) - Halpin, David; Hyland, Michael; Blake, Susan; Seamark, Clare; Pinnuck, Margaret; Ward, David; Whalley, Ben; Greaves, Colin; Hawkins, Adam; Seamark, David
Objectives: To determine the importance of fear and anxiety at the time of an exacerbation of chronic obstructive pulmonary disease. To assess the influence of carers and health professionals on this fear and anxiety. Design: A qualitative study to elicit the views of patients and their carers during a hospital admission for exacerbations of chronic obstructive pulmonary disease. Setting: Interviews were conducted in a District General Hospital. Participants: Twenty patients were interviewed shortly after admission to hospital with an exacerbation. Main outcome measures: Key themes were identified using cross-sectional thematic analysis of transcripts where commonalities and differences were identified. Results: Four themes emerged: panic and fear; anxiety management techniques used during an exacerbation; intervention from family members and carers; response to medical services. Conclusion: Panic and fear are important emotions prior to admission. Many patients recognised the link between panic-fear and a worsening of symptoms, and some were able to use self-management techniques to reduce their panic-fear. Some relatives were seen as helping and others exacerbating the symptoms of panic-fear. The emergency services were seen as positive: providing reassurance and a sense of safety. How best to help patients with chronic obstructive pulmonary disease manage panic and fear remains a challenge.